Collapse Behaviour of a Concrete-Filled Steel Tubular Column Steel Beam Frame under Impact Loading. (23rd April 2021) - Song, Lian; Hu, Hao; He, Jian; Chen, Xu; Tu, Xi
Abstract : The progressive collapse of a concrete-filled steel tubular (CFST) frame structure is studied subjected to impact loading of vehicle by the finite-element software ABAQUS, in the direct simulation method (DS) and alternate path method (AP), respectively. Firstly, a total of 14 reference specimens including 8 hollow steel tubes and 6 CFST specimens were numerically simulated under transverse impact loading for verification of finite-element models, which were compared with the existing test results, confirming the overall similarity between them. Secondly, a finite-element analysis (FEA) model is established to predict the impact behaviour of a five-storey and three-span composite frame which was composed of CFST columns and steel beams under impact vehicle loading. The failure mode, internal force-time curve, displacement-time curve, and mechanical performance of the CFST frame were obtained through analyzing. Finally, it is concluded that the result by the DS method is closer to the actual condition and the collapse process of the structure under impact load can be relatively accurately described; however, the AP method is not.